PENGELOLAAN BANK SAMPAH DI KABUPATEN BENGKALIS - M. Gilang Dirgantara; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Urban hygiene programs and waste management in general have been implemented by almost all city/district governments throughout the archipelago, including Mandau District. Mandau District as a center for trade, education, health and cultural development, is a place where tens of thousands of people live. This phenomenon has implications for all areas of urban life and one of them is the implication of increasing waste production. to overcome the problem, the local government's attention is still lacking in providing the facilities needed for smooth waste management, the lack of management supervision from the local government, the local government's lack of attention to the waste bank, especially in terms of marketing products that have been processed. Planning in the management of Pematang Pudu Bersih Waste Bank in general starts from short-term planning, medium-term planning, and long-term planning. This Clean Pematang Pudu Waste Bank can be said to be a pilot Waste Bank in Pematang Pudu Village, Mandau District, this is proven by the influence on other communities. The purpose of this study is to find out the management of the waste bank in Bengkalis Regency and find out what factors influence the management of the waste bank in Bengkalis Regency. This study uses a purposive sampling technique with a qualitative research type with a descriptive approach, the required data such as primary data and secondary data obtained through interviews, observations and documentation and then analyzed based on research problems. The results of this study indicate that the management of the Waste Bank in Bengkalis Regency is running well, while the supporting factors are the leadership of the head of a good waste bank and customer participation in managing waste is very high. Keywords: Management, Waste Bank, and planning